Gender Differences in Risk Factor and Clinical Outcome in Patients with Ischemic Stroke - Kwang Soo Kim (Kosin Medical Journal, 2014)
Abstract Objective: Gender is an important determinant for risk factors and outcomes of ischemic stroke. The aim of this study was to compare risk factors, and clinical outcomes after ischemic stroke between male and female patients. Methods: The hospital records of patients with ischemic stroke were reviewed retrospectively. Demographic data, stroke risk factors, clinical severities and outcomes after stroke were collected and compared between male and female patients. Stroke severity and clinical disability after ischemic stroke were evaluated by means of the National Institutes of Health Stroke Scale (NIHSS) and modified Rankin Scale (mRS) respectively. Results: Among 447 patients with ischemic stroke, 195 (43.6%) patients were women. The mean age at ischemic stroke was higher in women than in men (p<0.01). As compared to men, women had a significantly lower prevalence of hyperhomocysteinemia, smoking and drinking (all p<0.01). NIHSS and mRS scores were not different between the 2 genders. Conclusions: Profiles of risk factors differed between the 2 genders, with men having a higher prevalence of hyperhomocysteinemia, smoking and drinking. There were no gender differences in stroke severity and disability after ischemic stroke.